Water deprivation-induced sodium appetite and differential expression of encephalic c-Fos immunoreactivity in the spontaneously hypertensive rat - Pereira-Derderian, Daniela T. B. [UNESP]; Vendramini, Regina Célia [UNESP]; Menani, José Vanderlei [UNESP]; De Luca, Laurival A. [UNESP] (Amer Physiological Soc, 2010)
Pereira-Derderian DT, Vendramini RC, Menani JV, de Luca Jr. LA. Water deprivation-induced sodium appetite and differential expression of encephalic c-Fos immunoreactivity in the spontaneously hypertensive rat. Am J Physiol Regul Integr Comp Physiol 298: R1298-R1309, 2010. First published March 3, 2010; doi: 10.1152/ajpregu.00359.2009.-The spontaneously hypertensive rat (SHR) has an intense consumption of NaCl solution. Water deprivation (WD) followed by water intake to satiety induces partial rehydration (PR)-the WD-PR protocol-and sodium appetite. In the present work, WD produced similar water intake and no alterations in arterial pressure among spontaneously hypertensive rat (SHR), Wistar-Kyoto, and Holtzman strains. It also increased the number of cells with positive c-Fos immunoreactivity (Fos-IR) in the lamina terminalis and in the hypothalamic supraoptic (SON) and paraventricular (parvocellular, PVNp) nucleus in these strains. The WD and WD-PR produced similar alterations in all strains in serum osmolality and protein, plasma renin activity, and sodium balance. The SHR ingested about 10 times more 0.3 M NaCl than normotensives strains in the sodium appetite test that follows WD-PR. After WD-PR, the Fos-IR persisted, elevated in the lamina terminalis of all strains but notably in the subfornical organ of the SHR. The WD-PR reversed Fos-IR in the SON of all strains and in the PVNp of SHR. It induced Fos-IR in the area postrema and in the nucleus of the solitary tract (NTS), dorsal raphe, parabrachial (PBN), pre-locus coeruleus (pre-LC), suprachiasmatic, and central amygdalar nucleus of all strains. This effect was bigger in the caudal-NTS, pre-LC, and medial-PBN of SHRs. The results indicate that WD-PR increases cell activity in the forebrain and hindbrain areas that control sodium appetite in the rat. They also suggest that increased cell activity in facilitatory brain areas precedes the intense 0.3 M NaCl intake of the SHR in the sodium appetite test.
Keywords: dehydration; thirst; sodium intake; brain mapping; angiotensin